Language Models and Multi-Hop Reasoning in Scientific Question Answering - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: How do language models handle multi-hop reasoning chains in scientific question answering v9. 12 claims were extracted from source literature; 3 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 5.2/10. This report is a machine-generated literature synthesis and does not constitute original research.
Machine-generated literature synthesis.